50 psychology classics - "Butler - Bowdon, Tom" (London, 2007)
50 Psychology Classics looks at some of the most intriguing questions relating to what motivates us, what makes us feel and act in certain ways, how our brains work, and how we create a sense of self. This edition includes contemporary classics like Thinking, Fast and Slow; Quiet and The Marshmallow Test.
Keywords: Psychological literature